Literature Review: Utilization of Binanong Leaves and Red Betel Leaves for Healing Perineal Wounds - Yulina Dwi Hastuty; Mawar Ariska (Journal of Midwifery and Nursing, 2022)
Perineal wounds is an injury to the perineum that occurs when the baby is born either spontaneously or using tools or procedures. Perineal wound care aims to prevent infection, increase comfort and prepare for healing. The use of traditional methods is still carried out by the Indonesian people in the treatment of perineal wounds by making antiseptic decoctions such as binahong leaves and red betel leaves. Several studies have stated that the active content in binahong leaves can accelerate the wound healing process. Likewise with betel leaf. However, it is not known which one is more effective between the two. This literature study aims to determine the effectiveness of binahong leaf decoction and red betel leaf decoction on the perineal wound healing process in postpartum mothers. Based on the data used to collect information, Mendelay, PubMed, Science Direct and Google Scholar with the keywords Binahong Leaf Perineal Wound Healing, Red Betel Leaf and Postpartum Perineal Wounds. The results showed that presenting red betel leaf was more effective for healing perineal wounds with binahong leaves. Perineal wound healing time using red betel leaf decoction is 4-5 days on average, while binahong leaves are 6-7 days on average.